2013
DOI: 10.1161/circinterventions.112.000429
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Trajectory After Transcatheter Aortic Valve Implantation

Abstract: Background-Transcatheter aortic valve implantation (TAVI) is known to be associated with silent cerebral injury, which could contribute to cognitive impairment. Considering its increasing use, thorough longitudinal investigation of cognitive trajectory after TAVI is pivotal. Methods and Results-Repeatable battery for the assessment of neuropsychological status was performed before (E1), 3 days (E2), 3 months (E3), 1 (E4) year, and 2 years (E5) after TAVI. Baseline characteristics, procedural data, imaging para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
85
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 40 publications
7
85
0
1
Order By: Relevance
“…Cerebral embolization, demonstrated by new ischemic defects detected by magnetic resonance imaging is highly frequent but it has limited clinical manifestation [25]. This study has also shown that the size of the ischemic defects, when they occur, are bigger in the surgical group in comparison with TAVR patients [26].…”
mentioning
confidence: 64%
“…Cerebral embolization, demonstrated by new ischemic defects detected by magnetic resonance imaging is highly frequent but it has limited clinical manifestation [25]. This study has also shown that the size of the ischemic defects, when they occur, are bigger in the surgical group in comparison with TAVR patients [26].…”
mentioning
confidence: 64%
“…Currently, there are a wide variety of neurocognitive tests, commonly termed the Neurocognitive Assessment Battery. 35 Some of the EPD trials have used these proposed batteries of neurocognitive tests, which have been used in previous clinical trials and have been piloted in the PARTNER II study. Similar studies in older populations have placed neurocognitive function testing as a primary outcome, pointing out that in this population the quality of life is not less important than life itself.…”
Section: Neurocognitive Testingmentioning
confidence: 99%
“…Both SAVR and TAVR literature reported cognitive decline after the operation, but the clinical implication of these deficits is not well established. [7][8][9] This uncertainty is also true for silent neurological events (ie, events recorded by imaging modalities with no apparent clinical symptoms). Messé et al report a 54% incidence of silent brain infarcts that were demonstrated by diffusion-weighted imaging after the procedure in patients with no clinical neurological event.…”
Section: Article See P 2253mentioning
confidence: 99%